Levels of IGF-1 and Their Relationship with Bone Mineral Density in the Premenopausal Women with Fibromyalgia Syndrome - Onur Armağan; Esra Sırmagül; Ayşe Ekim; Başar Sırmagül; Funda Taşçıoğlu; Cengiz Öner (Archives of Rheumatology, 2008)
Objective: The present study aims to compare bone mineral density (BMD) of healthy female patients with that of females with fibromyalgia syndrome (FMS), as well as to determine the relationship between insulin-like growth factor-1 (IGF-1) and BMD. Materials and Methods: Twenty-seven premenopausal women with FMS and 21 age-matched female controls were included in the study. Body mass index (BMI), IGF-1 and osteocalcin levels were assessed for all the cases. BMD measurements of the femoral neck and lumbar spine were done by using dual-energy X-ray absorptiometry. Results: Lomber and femoral bone mineral density were significantly lower in FMS patients compared with controls (p<0.001). Serum concentrations of IGF-1 were significantly lower in FMS than those in healthy females (p<0.01). There was a significant correlation between IGF-1 and BMD (trochanteric and lumbar spine) in FMS patients. No difference was found between the groups with respect to serum osteocalcine levels. Conclusions: The results of the present study shows that routine BMD measurements should be done in premenopausal FMS patients, especially who have low levels of IGF-1. (Rheumatism 2008; 23: 118-23)